2015
DOI: 10.1021/bk-2015-1197.ch007
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-Oxide Solids as Water-Oxidation Electrocatalysts: The Effect of Intercalating Cations

Abstract: A set of birnessite-type manganese oxides with both monovalent alkaline cations (Li + , Na + , K + , Rb + or Cs +) and divalent alkaline-earth cations (Ca 2+ or Mg 2+) has been synthesized using electrolytic deposition methods. X-ray diffraction gives typical birnessite-type patterns, with diffraction peaks at 2θ = 12.01°and 24.7°assigned to (001) and (002) planes. Electron paramagnetic resonance spectra suggest differences in the stability of Mn(III) species in manganese-oxide layer, which is more stable in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Having synthesized the above sets of biogenic MnO x with diverse morphologies and structures, we employed them as electrocatalysts for water-oxidation reactions as previous reports suggested that synthetic MnO x with varying morphologies show varying OER activities. ,,, Both linear sweep voltammetric (LSV) and chronoamperometric (CA) studies were performed. As shown in Figure , all these biogenic MnO x show activities for anodic O 2 evolution, i.e., employing smaller overpotentials (η < 880 mV at 8.3 A/g·cm 2 , normal hydrogen electrode which is used through this paper) than that of the bare FTO electrode (η > 930 mV at 8.3 A/g·cm 2 vs NHE, Figure A) and showing higher CA current density at 1.6 V (vs NHE) (Figure B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Having synthesized the above sets of biogenic MnO x with diverse morphologies and structures, we employed them as electrocatalysts for water-oxidation reactions as previous reports suggested that synthetic MnO x with varying morphologies show varying OER activities. ,,, Both linear sweep voltammetric (LSV) and chronoamperometric (CA) studies were performed. As shown in Figure , all these biogenic MnO x show activities for anodic O 2 evolution, i.e., employing smaller overpotentials (η < 880 mV at 8.3 A/g·cm 2 , normal hydrogen electrode which is used through this paper) than that of the bare FTO electrode (η > 930 mV at 8.3 A/g·cm 2 vs NHE, Figure A) and showing higher CA current density at 1.6 V (vs NHE) (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…The monoclinic birnessite sample was prepared using a protocol that was modified from previously reported procedures. , Electrodeposition was performed on a Princeton Applied Research (Oak Ridge, TN) Model 263 A potentiostat/galvanostat and was analyzed using the PowerStep software package in a three-electrode system. The three-electrode system contains a fluorine-doped tin oxide-coated glass (FTO; Sigma-Aldrich, MO) as the working electrode, a nickel foam (MTI Corp., CA) as the counter electrode, and Ag/AgCl in 3 M NaCl (0.203 V vs NHE; BASi, IN) as the reference electrode.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations